2020
DOI: 10.1093/ehjci/ehaa946.0605
|View full text |Cite
|
Sign up to set email alerts
|

Cryoballoon pulmonary-vein isolation for atrial fibrillation with heart failure: results from a single-center cohort

Abstract: Background Atrial fibrillation (AF) and heart failure (HF) are of growing prevalence and increasing mortality. Radiofrequency ablation is safe and effective for patients with AF and HF. Prognosis might be improved in patients treated. However, there is no prospective trial investigating efficacy and safety of cryoballon ablation in patients with AF and HF. Objective To prospectively compare cryoballoon ablation in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The knowledge about concomitant risk factors such as SDB status in AF patients is important to approximate success rates of interventions [20] , [21] , [22] , [23] . AF ablation is effective and safe in obese and diabetic patients with and without SDB [24] , [25] , [26] , [27] . Observational studies and meta -analyses showed that appropriate SDB treatment may improve rhythm control in AF patients [28] .…”
mentioning
confidence: 99%
“…The knowledge about concomitant risk factors such as SDB status in AF patients is important to approximate success rates of interventions [20] , [21] , [22] , [23] . AF ablation is effective and safe in obese and diabetic patients with and without SDB [24] , [25] , [26] , [27] . Observational studies and meta -analyses showed that appropriate SDB treatment may improve rhythm control in AF patients [28] .…”
mentioning
confidence: 99%